(NkOLESO SUDXBY(B: [(NrASSKAZ(B] / s - (NbULGAKOW(B, (NmIHAIL aFANASXEWI^s ((NmOSKWA(B: s (NsOWREMENNIK(B, s, 1990)
(Nw SBORNIKE NAIBOLEE POLNO PREDSTAWLENO TWOR^ESTWO mIHAILA aFANASXEWI^A bULGAKOWA (B(1891-1940) (NZA (B1925-1927 (NGODY(B. (N|TO I KOROTKIE GAZETNYE FELXETONY(B, (NI RASSKAZY IZ (B"(NzAPISOK @NOGO WRA^A(B", (NI ZAWOEWAW[IE W POSLEDNIE GODY POPULQRNOSTX [IROKOGO ^ITATELQ POWESTI (B"(NsOBA^XE SERDCE(B" (NI (B"(NrOKOWYE QJCA(B".s
(NsOBA^XE SERDCE(B, (NrOKOWYE QJCAs
rus
Keywords: (NpOWESTX(B, (NRASSKAZYs; (NfELXETONYs